Understanding the Potential Benefits of Cannabidiol for Patients With Schizophrenia: A Narrative Review. Issue 1 (28th November 2021) - Dyck, Garrison J B; Maayah, Zaid H; Eurich, Dean T; Dyck, Jason R B
Abstract: Research suggests that cannabis-derived delta-9-tetrahydrocannabinol can be linked to the worsening of psychosis and/or other symptoms of schizophrenia. However, studies have shown that another major cannabinoid found in cannabis, cannabidiol (CBD), may be a potential alternative or adjunctive treatment for psychosis and schizophrenia. As such, herein we review the relevant literature relating to the safety and efficacy of CBD treatment in patients with schizophrenia, including the effects of CBD in treating the positive, negative, and cognitive symptoms of the disorder, as well as the molecular mechanisms by which CBD can reduce schizophrenic symptoms. The potential utility of CBD for mitigating cannabis cravings and cannabis withdrawal in this patient population will also be reviewed. Lastly, the dosing, method of drug delivery, length of treatment, and adverse effects of CBD in patients with schizophrenia are discussed. Thus, the goal of this narrative review is to help clinicians and researchers better understand the risks and benefits of this potential therapy for this patient population.